Chiral heterobimetallic chains from a dicyanideferrite building block including a π-conjugated TTF annulated ligand. Issue 42 (23rd June 2016) - Cui, Long; Lv, Zhong-Peng; Leong, Chanel F.; Ru, Jing; D'Alessandro, Deanna M.; Song, You; Zuo, Jing-Lin
Abstract : Two enantiopure 1D complexes were synthesized from the dicyanideferrite building block with a π-conjugated TTF annulated ligand. A field-induced magnetic phase transition is observed ( T N = 4.8 K) for compound2 -( SS ). Abstract : The π-conjugated tetrathiafulvalene (TTF) annulated ligand was introduced into a dicyanometallate for the first time, leading to the synthesis of the versatile redox-active dicyanideferrite building block [( n -Bu)4 N][Fe(TTFbp)(CN)2 ] (H2 TTFbp = N -(2-(4, 5-bis(methylthio)-1, 3-dithiol-2-ylidene)-5-(picolinamido) benzo[ d ][1, 3]dithiol-6-yl) picol inamide). The incorporation of the new precursor with chiral Mn III Schiff-base complexes resulted in two enantiopure one-dimensional complexes, [Mn(( R, R )-salphen)Fe(TTFbp)(CN)2 ] n (2 -( RR )) and [Mn(( S, S )-salphen)Fe(TTFbp)(CN)2 ] n (2 -( SS )) (Salphen = N, N ′-1, 2-diphenylethylene-bis(salicylideneiminato) dianion), which were synthesized and structurally characterized. Circular dichroism (CD) and vibrational circular dichroism (VCD) spectra confirmed the enantiomeric nature of the optically active complexes, and structural analyses revealed the formation of neutral cyanide-bridged double chains in2 -( RR ) and2 -( SS ). Solution and solid state CV studies revealed the redox-active characteristics of the complexes. Antiferromagnetic couplings were detected between Fe III and Mn III centers within a chain, and a field-induced magnetic phase transition was observed ( T N = 4.8 K). The introduction of electroactivity and chirality into cyanide-bridged complexes with interesting magnetic properties leads the way towards new multifunctional materials.